Harnessing Bacillus subtilis Spore Surface Display (BSSD) Technology for Mucosal Vaccines and Drug Delivery: Innovations in Respiratory Virus Immunization - Howra Bahrulolum; Parisa Beyranvand; Gholamreza Ahmadian (Drugs and Drug Candidates)
Respiratory viruses present significant global health challenges due to their rapid evolution, efficient transmission, and zoonotic potential. These viruses primarily spread through aerosols and droplets, infecting respiratory epithelial cells and causing diseases of varying severity. While traditional intramuscular vaccines are effective in reducing severe illness and mortality, they often fail to induce sufficient mucosal immunity, thereby limiting their capacity to prevent viral transmission. Mucosal vaccines, which specifically target the respiratory tract’s mucosal surfaces, enhance the production of secretory IgA (sIgA) antibodies, neutralize pathogens, and promote the activation of tissue-resident memory B cells (BrMs) and local T cell responses, leading to more effective pathogen clearance and reduced disease severity. Bacillus subtilis spore surface display (BSSD) technology is emerging as a promising platform for the development of mucosal vaccines. By harnessing the stability and robustness of Bacillus subtilis spores to present antigens on their surface, BSSD technology offers several advantages, including enhanced stability, cost-effectiveness, and the ability to induce strong local immune responses. Furthermore, the application of BSSD technology in drug delivery systems opens new avenues for improving patient compliance and therapeutic efficacy in treating respiratory infections by directly targeting mucosal sites. This review examines the potential of BSSD technology in advancing mucosal vaccine development and explores its applications as a versatile drug delivery platform for combating respiratory viral infections.